ANALISIS KINERJA GURU SMK NEGERI 1 GEDONG TATAAN KABUPATEN PESAWARAN - Hazairin Habe (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
The problem in this study is whether motivation and Managerial Supervision affect teacherperformance at SMK Negeri 1 Gedong Tataan Kabupaten Pesawaran. This study aims to determine theeffect of motivation and Managerial Supervision on teacher performance. The hypothesis formulated isthat there is an influence of motivation and managerial supervision on teacher performance bothpartially and simultaneously. The sample used in this study amounted to 95 teachers.The results of partial hypothesis testing prove that motivation affects teacher performance, aswell as managerial supervision has a positive effect on teacher performance. Hypothesis testingsimultaneously motivation variables and managerial supervision variables have a positive effect onteacher performance. The results of the determination test show that simultaneously the teacherperformance variables are able to be explained by motivation variables and Managerial Supervision of85.3%, the remaining 14.7% are other variables not examined.